2021
DOI: 10.3389/fnagi.2020.598242
|View full text |Cite
|
Sign up to set email alerts
|

Early Segmental White Matter Fascicle Microstructural Damage Predicts the Corresponding Cognitive Domain Impairment in Cerebral Small Vessel Disease Patients by Automated Fiber Quantification

Abstract: Objective: To characterize earlier damage pattern of white matter (WM) microstructure in cerebral small vessel disease (CSVD) and its relationship with cognitive domain dysfunction.Methods: A total of 144 CSVD patients and 100 healthy controls who underwent neuropsychological measurements and diffusion tensor imaging (DTI) examination were recruited. Cognitive function, emotion, and gait were assessed in each participant. The automated fiber quantification (AFQ) technique was used to extract different fiber pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 60 publications
0
40
0
Order By: Relevance
“…Besides, a study related to reduced attention of young bilingual adults showed that the integrity of the white matter fibers connecting the anterior cingulate cortex and the frontal regions was decreased, and this manifestation only exists in the right hemisphere (Mamiya et al, 2018). Similarly, Huang et al (2020) also reported that the right ATR was associated with executive function in cerebral small vessel disease patients.…”
Section: Discussionmentioning
confidence: 95%
“…Besides, a study related to reduced attention of young bilingual adults showed that the integrity of the white matter fibers connecting the anterior cingulate cortex and the frontal regions was decreased, and this manifestation only exists in the right hemisphere (Mamiya et al, 2018). Similarly, Huang et al (2020) also reported that the right ATR was associated with executive function in cerebral small vessel disease patients.…”
Section: Discussionmentioning
confidence: 95%
“…Our results extend the present literature on white matter abnormalities and their impacts on processing speed in CSVD, providing evidence for the importance of the SWM. A number of CSVD studies have found strong associations of cognitive performance with diffusion MRI measures in the DWM (O’Sullivan et al ., 2005; Quinque et al ., 2012; Tuladhar et al ., 2015; Chen et al ., 2019; Huang et al ., 2020; Liu et al ., 2020; Vergoossen et al ., 2021) and in white matter areas without visible WMH (M. O’Sullivan et al ., 2004; M.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional diffusion measures (e.g., FA, MD) (Michael O'Sullivan et al, 2004;O'Sullivan et al, 2005;Nitkunan et al, 2008;Schmidt et al, 2010;Quinque et al, 2012;Lawrence et al, 2013;Tuladhar et al, 2015;Baykara et al, 2016;Moonen et al, 2017;Zeestraten et al, 2017;Tozer et al, 2018;Chen et al, 2019;Wei et al, 2019;Huang et al, 2020;Liu et al, 2020;Du et al, 2021;Vergoossen et al, 2021) Advanced diffusion measures (e.g. FW, NODDI, DKI, IVIM) (Zhang, Wong, van de Haar, et al, 2017;Duering et al, 2018;Gesierich et al, 2020;Konieczny et al, 2021) Structural network measures (Lawrence et al, 2014;Reijmer et al, 2016;Tuladhar et al, 2016Tuladhar et al, , 2017Heinen et al, 2018;van Leijsen et al, 2019;Boot et al, 2020;Gesierich et al, 2020;Liu et al, 2020;Du et al, 2021) Study findings: White matter regions related to cognitive performance in CSVD…”
Section: Csvd Dmri Study Methodologymentioning
confidence: 99%
“…The following steps were used through MATLAB 2019a: normalized T1 images to template space and segmented images into gray matter, white matter, and cerebrospinal uid; visual inspection; the total intracranial volume was evaluated; check for data homogeneity; the Gaussian kernel of full width at half maximum 6 mm (FWHM = 6 mm) was used. The "brain volume/ intracranial volume (ICV) x 100%" was used to display WMHs, gray and white matter volume [19].…”
Section: Structural Datamentioning
confidence: 99%